Kompetensi Pedagogik Guru dalam Mengembangkan Potensi Bakat Siswa-siswi di MI. Al-Ihsan V/B Sentol Daya Pragaan Sumenep Tahun Pelajaran 2020-2021 - M. Shaleh (LPPM Politeknik Pratama, 2024)
Pedagogical competence is the teacher's ability to manage student learning which includes understanding students, designing and implementing learning, evaluating learning outcomes as well as developing students to actualize the various potentials that students have. Motivating students means encouraging students to increase their interest in learning so as to achieve optimal results. This research was conducted to find out what the pedagogical competence of MI teachers is. Al-Ihsan VB is good at developing curriculum, implementing learning, designing learning, using technology in learning, and facilitating the development of the potential of its students. The research subjects are MI teachers. Al-Ihsan VB where they have status as certified teachers. This research uses a descriptive method with a qualitative approach. Research data was collected through interviews, observation and documentation studies. Then the data is analyzed through descriptive means describing events in the field. The research results show that teachers who have been certified at MI. Al-Ihsan VB has been able to develop the learning implementation plan (RPP) that they prepare before carrying out the lesson and notes on the progress of student learning outcomes. They have chosen learning methods that suit the character and abilities of students. And they have been able to use technology well as a medium or learning tool. However, what is still an obstacle at the moment is that schools have not yet repaired media or technological equipment such as LCDs which are damaged. In order to develop the potential of MI teachers' students. Al-Ihsan VB carries out extra-curricular activities for students such as scout activities, studios and majlis taklim.